Design of the Exterior & Interior Car Body for Soekarno-Hatta Airport Railing Service - Agus Windharto (Institut Teknologi Sepuluh Nopember, 2014)
Transportation needs for Jakarta city to Soekarno- Hatta International Airport with a capacity of 54million passengers/year in 20012 and is expected to rise until 62million in the year 2014.Problems encountered are the traffic jams of Jakarta transportation that based on toll and highway access to the airport, resulting in energy inefficiency, pollution and loss of productivity. The Inconvenience of other transportation mode to the airport such as Damri Bus, Taxi and private car.The research objective are designing mode of transportation, speed, comfort, safe and new image for Soekarno-Hatta airport as Republic of Indonesia gateway. In order to reduce traffic congestion and improve access to the airport and from the airport to the city, the ARS (Airport Railing Service)/ KRL express(Electric Rail) executive class has a shorter duration of the traveling time (± 40 minutes) compared with other modes of transport (Bus, Taxi and private car) around 60-120 minutes.The research method is Design engineering and digital prototyping of exterior and interior design on the early stages, then digital-based integrated design for study of geometry (Lopas and cross section), ergonomics, styling (branding, color scheme, interior configuration).The results of this research are: three (3) alternate designs, a final exterior design, interior general arrangement, driver cab, lugage compartment, lavatory and digital signage design. Designs already approved by the operator (PT Railink Indonesia). The results of this study hopefully will become reference for National railway manufacturing industry (INKA) Madiun to be made prototype and series production.